GLOBAL RESEARCH DYNAMICS ABOUT PUBLIC DEBT: RISING PUBLIC DEBT AND THE EUROPEAN FISCAL UNION - Cecilia CIOCIRLAN (Annals of the "Ovidius" University of Constanţa. Political Science Series)
This paper aims to bring Romanian research on public debt into the international spotlight, contextualizing it within the rising global debt levels caused by recent economic crises, such as the global financial crisis and the Covid-19 pandemic. The main goal is to highlight the importance of local research, often overlooked, while analyzing public debt through both global and local lenses. The first part of the paper analyzes the intensifying effects of globalization, accelerated by the Covid-19 pandemic, and the shift in how public debt is perceived, with a growing focus on investments and budget deficits. It also examines the challenges faced by decision-makers in managing debt sustainability, particularly the tension between political priorities and fiscal realities. The second part provides an empirical analysis of recent studies on the rise of global public debt, political economy factors, and credit cycles. The third section outlines the difficulties in governing public debt in the European Union due to the absence of a fiscal union and explores the concept of an optimal monetary zone. One of the central political issues raised is the tendency of politicians, especially in advanced economies, to exploit public debt for short-term electoral gains.